Study of Cytotoxic and Photodynamic Activities of Dyads Composed of a Zinc Phthalocyanine Appended to an Organotin - Isabelle Toubia; Christophe Nguyen; Stéphane Diring; Marine Pays; Elodie Mattana; Philippe Arnoux; Céline Frochot; Magali Gary-Bobo; Marwan Kobeissi; Fabrice Odobel (MDPI AG, 2021)
The combination of photodynamic therapy and chemotherapy is a promising strategy to enhance cancer therapeutic efficacy and reduce drug resistance. In this study two zinc(II) phthalocyanine-tin(IV) conjugates linked by a triethylene glycol chain were synthesized and characterized. In these complexes, the zinc(II) phthalocyanine was used as a potential photosensitizer for PDT and the tin complex was selected as cytostatic moiety. The two dyads composed of zinc(II) phthalocyanine and tin complexes exhibited high cytotoxicity, in absence of light stimulation, against MCF-7 human breast cancer cells with low LC50 values in the range of 0.016-0.453 µM. In addition, these complexes showed superior cytotoxicity than their mixture of equimolar component, accompanied with a higher activity towards cancer cells compared to human healthy fibroblasts. However, under irradiation of the zinc phthalocyanine unit (at 650 nm) no photodynamic activity could be detected, due to the most likely quenching of zinc(II) phthalocyanine singlet excited state by the nearby tin complex according to a photoinduced electron transfer process. This study demonstrates the potential of heterometallic anticancer chemotherapeutics composed of a zinc phthalocyanine and tin complex, and it highlights that the development of such conjugates requires that the sensitizer preserves its photophysical properties and in particular its singlet oxygen sensitization ability in the conjugate in order to combine the PDT activity with the cytotoxicity of the anticancer drug.